The dean of health sciences and Universidad Centroccidental Lisandro Alvarado, sixty years moving forward together (Gestión y Gerencia, 2022)
The history of the Deanship of Health Sciences Universidad Centroccidental Lisandro Alvarado (UCLA) is briefly developed in the 60 years of academy of the Universidad Centroccidental Lisandro Alvarado, its first promotions of Medicine and Nursing, its authorities, departments, postgraduate studies, research. Some anecdotes of teachers and students that make an institution that struggles, lives, throbs and projects itself over time as one of the five best universities in Venezuela proud.
Keywords: Anniversary; graduation; medicine; nursing